Closing the Digital Gap in Africa - Bon, Anna (International Higher Education, 2011)
African universities need information and communication technologies (ICTs) to enhance teaching and learning, to participate in collaborative research networks and to deliver high-level ICT experts for society. By adopting ICTs in an innovative way, higher education in Africa can pave the road towards the global knowledge society.